1996
DOI: 10.1051/gse:19960106
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of age and weight at puberty, ovulation rate and embryo survival in gilts and relations with production traits

Abstract: 214.9 ! 1.4, 197.8 ! 3.3 and 190.1 ! 2.1 days for AFE, 116.1 ± 0.9, 102.5 ± 2.2 and 97.7 ± 1.4 kg for WFE, 14.4 ± 0.1, 13.0 0.3 and 13.9 ± 0.2 for OR and 9.6 ! 0.1, 9.6 f 0.4 and 10.5 ! 0.3 for NE in LW, LF

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
11
2
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 26 publications
7
11
2
1
Order By: Relevance
“…This was particularly true for direct effects, as a single significant genetic correlation was obtained for OR with AGET. In particular, the genetic correlation between OR and ADG was close to zero, unlike the results of Young et al (1977) and Bidanel et al (1996), who reported significant positive genetic correlations between the 2 traits (0.41 and 0.20, respectively). Ruiz-Flores and Johnson (2001) reported a strong positive direct genetic correlation between birth weight and OR (0.44), but much lower values for subsequent BW and backfat thickness.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…This was particularly true for direct effects, as a single significant genetic correlation was obtained for OR with AGET. In particular, the genetic correlation between OR and ADG was close to zero, unlike the results of Young et al (1977) and Bidanel et al (1996), who reported significant positive genetic correlations between the 2 traits (0.41 and 0.20, respectively). Ruiz-Flores and Johnson (2001) reported a strong positive direct genetic correlation between birth weight and OR (0.44), but much lower values for subsequent BW and backfat thickness.…”
Section: Discussioncontrasting
confidence: 87%
“…They also obtained estimates of maternal genetic correlations with piglet BW at birth and at weaning (−0.26 and 0.11, respectively) that were very similar to those reported here. The low direct genetic correlation between most growth traits and PS is also consistent with the value obtained by Bidanel et al (1996) and the estimates between growth traits and litter size at birth reported by Ruiz-Flores and Johnson (2001). There do not seem to be any previous estimates of the maternal genetic correlations between PS and growth traits in the literature, the only related result being the strong negative estimates between growth and litter size obtained in the Nebraska experiment (Ruiz-Flores and Johnson, 2001).…”
Section: Discussionsupporting
confidence: 86%
“…Even though prenatal survival decreases when the ovulation rate increases, there are positive phenotypic and genetic correlations between ovulation rate and litter size in European breeds (Haley and Lee, 1992;Bidanel et al, 1996). Ovulation rate can be improved through genetic selection (Cunningham et al, 1979, Bidanel et al, 1996 and through nutritional and hormonal manipulation. Ovulation is the last step of a slow and complex process of growth and maturation of the follicles.…”
Section: Introductionmentioning
confidence: 99%
“…This was also confirmed in the research of Tummaruk et al (2001), Čechova and Tvrdoň (2006), and Mijatović et al (2009). Gilts reach puberty with different body composition, however puberty is initiated by metabolic signals, among which special significance for growth and differentiation of cells plays leptin and insulin-like growth factor-I (IGF-I; Bidanel et al, 1996;Barb et al, 1997;Roongsitthichai and Tummaruk, 2014). Some authors have emphasized that the traits associated with reproduction should be taken into account in the development of breeding strategies aimed at improving the fattening and slaughter traits (Kuehn et al, 2009;McPherson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%